Deuterium retention in tungsten simultaneously damaged by high energy W ions and loaded by D atoms. (August 2017) - Markelj, S.; Schwarz-Selinger, T.; Založnik, A.; Kelemen, M.; Vavpetič, P.; Pelicon, P.; Hodille, E.; Grisolia, C.
Highlights: Deuterium retention measured for the first time in tungsten samples simultaneously damaged by high energy W ions and loaded by D atoms. Synergistic effects between damage creation and presence of hydrogen were observed. Increased D retention obtained for simultaneous damaging and D exposure as compared to sequential damaging at high temperatures. Competition between defect annihilation and defect stabilization with D was observed. Thermal D de-trapping is the dominant process at high temperatures. Abstract: Deuterium retention was for the first time measured in tungsten samples simultaneously irradiated by W ions and exposed to D atoms at five different temperatures from 450 K to 1000 K. In order to obtain information on the defect concentration, samples were afterwards exposed to D atoms at 600 K to populate the created defects. The results were compared to different sequential damaging/exposure experiments. Synergistic effects were observed, namely, higher D concentrations were found in the case of simultaneous damaging and D-atom loading as compared to sequential damaging at elevated temperatures and populating the defects afterwards. However, the deuterium retention is still lower as compared to sequential damaging at room temperature and post-damaging annealing. The observations are explained by stabilization of defects by the presence of solute hydrogen in the bulk that would annihilate at high temperatures without the presence of hydrogen. Results of simultaneous W-ion damaging and D exposure at elevated temperatures were also compared to a sequential experiment of W-ion damaging at room temperature and then D-atom loading at high temperatures showing that thermal D de-trapping dominates deuterium retention at high temperatures.